2015
DOI: 10.1074/jbc.m115.648659
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Regulates the Ubiquitin-independent Degradation of Yeast Pah1 Phosphatidate Phosphatase by the 20S Proteasome

Abstract: Background: Yeast Pah1 phosphatidate phosphatase required for triacylglycerol synthesis is subject to proteasome-mediated degradation. Results: Pah1 is degraded by the 20S proteasome in a ubiquitin-independent manner that is governed by its phosphorylation state. Conclusion: 20S proteasomal degradation of Pah1 is regulated by phosphorylation and dephosphorylation. Significance: Pah1 function in lipid metabolism is regulated by the 20S proteasome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 104 publications
7
76
0
Order By: Relevance
“…Using purified preparations of proteasome and a nonphosphorylated version of Pah1 purified from E. coli, in vitro experiments showed that Pah1 is degraded by the 20S proteasome in a ubiquitin-independent manner. Whereas phosphorylation by protein kinase CKII did not affect the susceptibility of Pah1 to 20S proteasome-mediated degradation (46), phosphorylation by protein kinase C slightly increased Pah1 instability and phosphorylation by protein kinase A or Pho85-Pho80 kinase attenuated Pah1 degradation (17). Consistent with this observation, in vivo analysis using nonphosphorylatable variants of Pah1 showed that abrogation of protein kinase C phosphorylation prevented the decrease in abundance of a Pah1 variant refractory to Pho85-Pho80 kinase phosphorylation (45).…”
Section: Pa Phosphatase Balances Membrane Expansion With Lipid Storagesupporting
confidence: 69%
See 2 more Smart Citations
“…Using purified preparations of proteasome and a nonphosphorylated version of Pah1 purified from E. coli, in vitro experiments showed that Pah1 is degraded by the 20S proteasome in a ubiquitin-independent manner. Whereas phosphorylation by protein kinase CKII did not affect the susceptibility of Pah1 to 20S proteasome-mediated degradation (46), phosphorylation by protein kinase C slightly increased Pah1 instability and phosphorylation by protein kinase A or Pho85-Pho80 kinase attenuated Pah1 degradation (17). Consistent with this observation, in vivo analysis using nonphosphorylatable variants of Pah1 showed that abrogation of protein kinase C phosphorylation prevented the decrease in abundance of a Pah1 variant refractory to Pho85-Pho80 kinase phosphorylation (45).…”
Section: Pa Phosphatase Balances Membrane Expansion With Lipid Storagesupporting
confidence: 69%
“…Consistent with this observation, in vivo analysis using nonphosphorylatable variants of Pah1 showed that abrogation of protein kinase C phosphorylation prevented the decrease in abundance of a Pah1 variant refractory to Pho85-Pho80 kinase phosphorylation (45). Using Pah1 purified from S. cerevisiae, which would be phosphorylated, it was observed that dephosphorylation by Nem1/Spo7 made Pah1 more susceptible to 20S proteasome degradation (17). The accumulated evidence suggests that changes in Pah1 phosphorylation are part of a sensitization mechanism whereby fully active dephosphorylated Pah1 becomes more susceptible to proteasome degradation.…”
Section: Pa Phosphatase Balances Membrane Expansion With Lipid Storagesupporting
confidence: 57%
See 1 more Smart Citation
“…The phosphorylation of Pah1 by Pkc1 does not affect its location or PA phosphatase activity, but instead affects its stability (3). The Pkc1 phosphorylation of Pah1, which is favored when the enzyme is not phosphorylated on the target sites of Pho85 and Cdc28, promotes its degradation by the 20S proteasome (3,59). Here we showed that the abundance of Pah1 is stabilized in cho1 mutant cells lacking the ability to synthesize PS, which indirectly supports the notion that PS regulates Pkc1 activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, the phosphorylation of Pah1 by rat brain PKC stimulates its degradation by the 20S proteasome (59). The phosphorylation-mediated degradation 32 P-labeled Nem1-TM and Spo7-TM in the polyacrylamide gel were transferred to a polyvinylidene difluoride membrane and then treated with HCl or L-1-tosylamido-2-phenylethyl chloromethyl ketone-treated trypsin.…”
Section: Pah1 Abundance Is Stabilized In Yeast Cells Lacking Psmentioning
confidence: 99%